Sexuality and associated risk factors in pregnant women - Paula Renata Amorim Lessa Soares; Cinthia Gondim Pereira Calou; Samila Gomes Ribeiro; Priscila de Souza Aquino; Paulo Cesar de Almeida; Ana Karina Bezerra Pinheiro (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to assess the sexual function of pregnant women and the influence of sociodemographic, obstetric, and behavioral factors on sexual dysfunction. Methods: cross-sectional study conducted with 141 pregnant women attended by the Single Health System and 120 by one private service, totaling 261 participants. A questionnaire containing sociodemographic, obstetric, and behavioral variables was applied, as well as the Female Sexual Function Index instrument, which was used to assess sexual function. Associations between variables and sexual dysfunction were made using the chi-square test, considering a statistically significant result when p < 0.05. Results: among the participants, 32.1% had sexual dysfunction, and the variables "age", "income" and "type of health service" had an influence on sexual dysfunction. The prevalence of pregnant women was between 21 and 30 years old (p < 0.001), with an income between 1 and 2 minimum wages (p = 0.048) and used the public health system network (p = 0.000). Conclusions: the factors associated with sexual dysfunction are "young pregnant women", "low income" and "attended in the public health service".